Log in to add a comment

Log in to add a comment

But a general Quadratic Equation can have acoefficient of a in front of x2:

ax2 + bx + c = 0

But that is easy to deal with ... just divide the whole equation by "a" first, then carry on:

x2 + (b/a)x + c/a = 0

Steps

Now we can solve a Quadratic Equation in 5 steps:

Step 1 Divide all terms by a (the coefficient of x2).

Step 2 Move the number term (c/a) to the right side of the equation.

Step 3 Complete the square on the left side of the equation and balance this by adding the same value to the right side of the equation.

We now have something that looks like (x + p)2 = q, which can be solved rather easily:

Step 4 Take the square root on both sides of the equation.Step 5 Subtract the number that remains on the left side of the equation to find x.

Examples

Here are two examples:

Example 1: Solve x2 + 4x + 1 = 0

Step 1 can be skipped in this example since the coefficient of x2 is 1

Step 2 Move the number term to the right side of the equation:

x2 + 4x = -1

Step 3 Complete the square on the left side of the equation and balance this by adding the same number to the right side of the equation.

(b/2)2 = (4/2)2 = 22 = 4

x2 + 4x + 4 = -1 + 4

(x + 2)2 = 3

Step 4 Take the square root on both sides of the equation:

x + 2 = ±√3 = ±1.73 (to 2 decimals)

Step 5 Subtract 2 from both sides:

x = ±1.73 – 2 = -3.73 or -0.27